Pengembangan Sistem Presensi Menggunakan Quick Response Code Dinamis untuk Madrasah Aliyah Al Mukhlisin Bandung - Erwin Susanto; Doan Perdana; Arif Indra Irawan; Rahmat Yasirandi (Universitas Syiah Kuala, 2019)
QR Code is the development of barcode technology that is able to store various kinds of information such as URLs, telephone numbers, SMS messages or other texts. At first, this technology was used for tracking vehicle parts in automotive industry. This study aims to develop an automatic presence system by utilizing QR Code technology, so that the presence process is more effective when compared to the presence manually since it was using digital technology. The implementation of the presence system with a QR Code was carried out at the Madrasah Aliyah Al Mukhlisin Bandung, to help solving some problems in school administration. The system was built in the form of an application installed on each teacher’s smartphone. Every student tapped their QR code image to confirm their attendance before the lesson begins. The advantage of this application was that it has an advantage on generated image of QR Code changed every user login. The results of development and testing showed that the developed system can be a solution for the presence process through the application of ICT technology with a QR Code. Testing of Quality of Service (QoS) on developed system was appropriate with ITU recommendation. Survey of users was applied to check the properness of application.